A Study on Regional Disparities and the Current Situation of Health Teacher Allocation in Chungcheongbuk-do - Bok Sang Yoon (The Korean Society for the Study of Local Education Management, 2026)
School health teachers play an important role in carrying out a wide range of health-related duties within individual schools. They are responsible for students’ health management, health education, and administrative tasks related to school health, among other responsibilities. In the absence of a school health teacher, these specialized duties are often assigned to general subject teachers, which may lead to a lack of professional expertise in school health services. However, disparities exist in the placement of health teachers depending on school size. In particular, small schools often face a lack of assigned health teachers, resulting in gaps in the effective implementation of essential health-related duties. Furthermore, such disparities in health teacher placement may be further exacerbated by regional population decline and depopulation. This study aims to examine regional disparities in health teacher placement by analyzing its spatial distribution and to investigate the actual conditions in school settings. The study focuses on all elementary schools in Chungcheongbuk-do, with the year 2026 set as the temporal scope. A choropleth map was used to visualize the presence or absence of health teacher assignment in each eup, myeon, and dong of Chungcheongbuk-do in order to identify regional disparities. In addition, field surveys and interviews were conducted to gain a detailed understanding of the operational conditions of schools without assigned health teachers. The placement of school health teachers, including responsibilities such as student health management and health education, is essential for ensuring a healthy school life for students. This study is expected to raise awareness of disparities in health teacher placement across schools and regions and contribute to a clearer understanding of the current situation.